A chalcogenide-based thermoelectric material and a preparation method thereof

Through the microwave rapid and controllable synthesis method, the problems of complex preparation process and high energy consumption of chalcogenide-based thermoelectric materials in the existing technology have been solved, and the preparation of chalcogenide-based thermoelectric materials with excellent thermoelectric properties and uniform structure and performance distribution has been achieved. , simplifying the process and reducing costs.

CN115124006BActive Publication Date: 2025-01-21QUZHOU RES INST OF ZHEJIANG UNIV +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210953934.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-10
Publication Date
2025-01-21
Estimated Expiration
2042-08-10

AI Technical Summary

Technical Problem

The prior art has problems in preparing chalcogen compound-based thermoelectric materials with long synthesis time, complex process, high energy consumption and difficulty in preparing materials with excellent thermoelectric properties, uniform structure and performance distribution, and a single phase.

Method used

Using a microwave rapid and controllable synthesis method, a first solution containing chalcogen elements or compounds and a reducing agent and a second solution of a cation source are prepared, mixed and reacted in a microwave synthesizer, followed by post-processing and hot-pressing sintering. Obtain chalcogenide-based thermoelectric materials.

Benefits of technology

This method has achieved the preparation of chalcogenide-based thermoelectric materials with low thermal conductivity, uniform structure and performance distribution, and a single phase, simplifying the process, shortening the preparation cycle, and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115124006B_ABST
    Figure CN115124006B_ABST
Patent Text Reader

Abstract

The present invention discloses a chalcogenide-based thermoelectric material and a preparation method thereof, and belongs to the technical field of thermoelectric material preparation. The chalcogenide-based thermoelectric materials are P-type and N-type thermoelectric materials, respectively, which are synthesized by microwave method, and further post-processed to obtain a pure chalcogenide phase. The synthesis process of the present invention is simple and efficient, and does not require an oxygen-free environment, and is easy to operate. Compared with the traditional oxygen-free liquid phase synthesis process, the energy consumption is significantly reduced, and the chalcogenide-based thermoelectric material obtained by microwave synthesis has a relatively pure phase and excellent performance. A certain concentration of vacancies is introduced into the chalcogenide material. ‑17 ~10 ‑19 , and further doped with different elements to reduce the thermal conductivity of the material and increase the Seebeck coefficient of the material, ultimately improving the thermoelectric properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a chalcogenide-based thermoelectric material and a preparation method thereof, belonging to the technical field of material synthesis and energy conversion. Background Art

[0002] Thermoelectric materials are functional materials that use the internal carrier movement characteristics of solids to achieve temperature difference power generation or thermoelectric refrigeration that converts heat energy into electricity, and have broad application prospects in the fields of temperature difference (waste heat) power generation and thermoelectric refrigeration. Sulfur compound-based thermoelectric materials have been widely concerned as a promising room temperature and medium temperature thermoelectric material because of their easy and controllable chemical synthesis and non-toxic and harmless constituent elements. Generally, sulfur compound-based thermoelectric materials have a low-symmetry structure at low temperatures, and undergo a phase transition as the temperature rises, transforming into a highly symmetric cubic phase with "electron-crystal, phonon-liquid" characteristics, and exhibiting excellent thermoelectric properties. However, the low-temperature thermoelectric performance of this type of material is still low, and the occurrence of phase transitions can easily lead to irreversible damage to the material or device, which is not conducive to commercial applications.

[0003] The conversion efficiency of thermoelectric devices depends on the thermoelectric materials themselves. Continuously improving the performance of existing thermoelectric materials and developing new high-performance thermoelectric material systems are important research directions in the field of thermoelectric materials. First of all, we should start with improving the preparation methods of thermoelectric materials. Traditional methods for preparing thermoelectric materials have the disadvantages of long synthesis time, complex processes, and high energy consumption. They are not conducive to maintaining a small grain size, and it is difficult to prepare chalcogenide-based thermoelectric materials with excellent thermoelectric properties, uniform organization and performance distribution, and a single phase using existing ordinary heating technology, which affects their thermoelectric performance. Therefore, it is urgent to develop a synthesis method that can be applied to chalcogenide-based thermoelectric materials. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the above prior art in preparing chalcogenide-based thermoelectric materials, and provide a method for preparing chalcogenide-based thermoelectric materials by microwave rapid controllable synthesis. By using the technical solution of the present invention, chalcogenide-based thermoelectric materials with low thermal conductivity, uniform organization and performance distribution, and single phase can be prepared, and the equipment and operation used are simple, the preparation cycle is short, and the cost is low.

[0005] In order to achieve the above object, the technical solution provided by the present invention is:

[0006] A method for preparing a chalcogenide thermoelectric material comprises the following steps:

[0007] (1) preparing a first solution and a second solution, wherein the first solution comprises a chalcogen element or compound and a reducing agent, wherein the concentration of the chalcogen element is 0.01 to 1 mol / L, and the molar ratio of the chalcogen element to the reducing agent is 1:0.5 to 7, and the chalcogen element or compound is at least one of tellurium, tellurium oxide, tellurium dioxide, sodium tellurite, selenium, selenium oxide, selenium dioxide, sodium selenite, sulfur, sodium sulfide, sodium sulfate, sodium sulfite, and thioacetamide. The second solution comprises a cation source, wherein the concentration of the cation source is 0.01 to 1 mol / L, and the cation source comprises at least one of silver nitrate, a mixture of silver nitrate and bismuth nitrate, a mixture of silver nitrate and lead nitrate, a mixture of silver nitrate and indium nitrate, a mixture of silver nitrate and copper nitrate, a mixture of stannous chloride and sodium hydroxide, a mixture of stannous chloride, sodium hydroxide and lead chloride, and a mixture of stannous chloride, sodium hydroxide and gallium chloride; the solvent of the first solution and the second solution is deionized water;

[0008] (2) mixing the first solution and the second solution in a volume ratio of 0.1 to 10:0.1 to 10, placing the mixture in a microwave synthesizer, and reacting for 1 to 180 minutes at a temperature of 30 to 300° C. and a stirring rate of 0 to 1800 rpm;

[0009] (3) adding the product obtained in step (2) to a reducing solution for post-treatment for 3-12 hours, and finally washing and centrifuging to finally obtain a sulfide-based thermoelectric material; the solvent of the reducing solution is a mixture of a non-polar solvent and a polar organic solvent in a volume ratio of 0.1-10:0.1-10; the solute is at least one of sodium borohydride, potassium borohydride, hydrazine hydrate, and lithium borohydride; the mass ratio of the solute to the two solvents is 0.001-0.5:1-5:1-5.

[0010] Furthermore, in the mixture of silver nitrate and bismuth nitrate, the mixture of silver nitrate and lead nitrate, and the mixture of silver nitrate and indium nitrate, the molar ratio of silver nitrate to bismuth nitrate, lead nitrate, indium nitrate or copper nitrate is 1:0.001-0.05.

[0011] Furthermore, in the mixture of stannous chloride and sodium hydroxide, the mixture of stannous chloride, sodium hydroxide and lead chloride, and the mixture of stannous chloride, sodium hydroxide and gallium chloride, the molar ratio of stannous chloride to sodium hydroxide is 1:2-30.

[0012] Furthermore, it also includes a hot pressing sintering molding step:

[0013] The obtained chalcogenide-based thermoelectric material is placed in a fixed shape mold, and maintained at a temperature of 100 to 1000° C., under a pressure of 10 to 220 MPa for 0.1 to 60 minutes. Then, the material is thermally stabilized at a temperature of 50 to 800° C. in an inert gas atmosphere for 0.1 to 12 hours, and demolded to obtain a molded chalcogenide-based thermoelectric material.

[0014] Furthermore, the first solution is prepared by the following method: adding a sulfide element or compound to deionized water at 20-100° C. and a pressure of 50 mbar or under an inert gas protection pressure of 0.01-0.05 MPa until dissolved to obtain a first solution;

[0015] The second solution is prepared by the following method:

[0016] Under the conditions of 20-100° C. and 50 mbar pressure or under the protection of an inert gas with a pressure of 0.01-0.05 MPa, a cation source is added to deionized water until it is dissolved to obtain a second solution.

[0017] Furthermore, the reducing agent is at least one of sodium borohydride, potassium borohydride, hydrazine hydrate and lithium borohydride.

[0018] Furthermore, the chalcogenide-based thermoelectric material is a black solid powder, is phase-pure, has no second-phase impurities after surface treatment, and has a yield of 80-99%.

[0019] A chalcogenide-based thermoelectric material prepared according to the above method, wherein the chalcogenide-based thermoelectric material is an N-type / P-type thermoelectric material and will not undergo a P-to-N-type transition before the phase change process.

[0020] The present invention takes advantage of the microwave synthesis process and attempts to study the mechanism of microwave heating and optimize the synthesis method; using an integrated digital camera to record images and videos, it is possible to track color changes and precipitation, check the dissolution of the matrix, and optimize stirring efficiency; the microwave reactor measures the temperature through an infrared temperature sensor, which is a rugged and reliable temperature control method that ensures absolutely accurate temperature measurement.

[0021] Microwave synthesis is a high-temperature self-propagating synthesis method using microwaves as the ignition source. Unlike traditional self-propagating synthesis methods, microwaves propagate from the inside out, heating high dielectric loss materials to a higher temperature in the microwave field to increase chemical activity to achieve the effect of reaction synthesis. Microwave heating has the following advantages over traditional heating technology:

[0022] (1) Integrity: Microwaves have penetrating power. When microwaves are transmitted to the surface of the heated material, they can quickly spread to the inside, so that the heated material is heated as a whole at the same time. Generally, the heated material can be heated evenly inside and outside. The traditional external heating method is to transmit heat from the outside to the inside, with a large temperature difference between the inside and the outside, and the heating speed is slow. In comparison, microwave heating can greatly shorten the heating time.

[0023] (2) Selectivity: Different substances have different absorption abilities for microwaves, i.e., their dielectric constants vary. Therefore, depending on the different electromagnetic properties of the substances themselves, their reactions under microwaves vary, which has the characteristics of selective heating and improves heating efficiency.

[0024] (3) Immediacy: Materials heated by microwaves heat up very quickly. The high conversion frequency of the microwave magnetic field produces radiation, causing the material to rotate and collide at a high frequency and begin to heat. Once the radiation stops, the heating reaction stops immediately. The heating process can be controlled at any time by controlling the power supply.

[0025] (4) Environmental protection: Traditional heating methods generally require a lot of energy and produce pollutants such as exhaust gas. However, microwave heating takes a short time, consumes less energy, and does not emit any pollutants, which has little impact on the environment.

[0026] Microwave heating has unparalleled advantages over traditional heating methods in the process of material synthesis and sintering. It can greatly shorten the synthesis cycle, improve the density of samples, and make the grains smaller and more evenly distributed. It can be seen that microwave synthesis methods have great development potential in the research of new materials and the exploration of new processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD diagrams of thermoelectric materials prepared in the examples of the present invention, (a) silver selenide; (b) tin telluride, the bottom vertical line is the characteristic peak of the tin telluride PDF card; (c) is the tin telluride after post-treatment in Example 8;

[0028] Figure 2 The local SEM microstructure of the thermoelectric material prepared in the embodiment of the present invention, (a) silver selenide; (b) tin telluride; the scale is 200 μm;

[0029] Figure 3 The electrical conductivity, Seebeck, thermal conductivity and dimensionless value test diagrams of the thermoelectric materials prepared in the embodiments of the present invention, (a)-(d) silver selenide; (b)-(d) tin telluride thermoelectric characteristic diagrams;

[0030] Figure 4 Thermal conductivity test diagram of thermoelectric materials prepared in the embodiments of the present invention, (a) silver selenide; (b) tin telluride. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with the accompanying drawings and embodiments.

[0033] Near-room-temperature silver selenide-based thermoelectric materials

[0034] Embodiment 1

[0035] Ag 2~x Se was synthesized by microwave method, and the specific preparation process is as follows:

[0036] 4mmol of selenium powder and 6mmol of sodium borohydride were dissolved in 10mL of deionized water at room temperature and under the protection of 0.01-0.05MPa inert gas, and stirred for 5 minutes to obtain a colorless and transparent first solution; at the same time, 7.5-9mmol of silver nitrate was dissolved in 10mL of deionized water at 20°C and under the protection of 0.01-0.05MPa inert gas to obtain a second solution; then, the second solution was quickly poured into the first solution and quickly moved to a microwave synthesizer to react at 300°C for 10 minutes; then, the reaction was terminated and the microwave synthesizer was cooled to room temperature, washed and precipitated with deionized water and ethanol for 3 times, collected by centrifugation, and the obtained sample was vacuum dried at 60°C for 12h to obtain dry Ag 2~x Se.

[0037] Embodiment 2

[0038] Bismuth-doped Ag 2~x Preparation of Se~y mol M (M=Bi) based samples, the specific preparation process is as follows:

[0039] Dissolve 4mmol of selenium powder and 6mmol of sodium borohydride in 10mL of deionized water at room temperature and under the protection of an inert gas of 0.01-0.05MPa, and stir for 5 minutes to obtain a colorless and transparent first solution; at the same time, ultrasonically dissolve y=1mol% or 2mol% of bismuth nitrate pentahydrate in 10mL of deionized water at 20°C and normal pressure, then add 7.5-9.0mmol of silver nitrate, stir and dissolve, then add 100-1000μL of nitric acid, stir for about 5min to obtain a clear second solution; then, quickly pour the second solution into the first solution and quickly move it to a microwave synthesizer at 90°C for reaction for 15 minutes. Subsequently, the reaction is terminated and the microwave synthesizer is cooled to room temperature, washed and precipitated 3 times with deionized water and ethanol, collected by centrifugation, and the obtained sample is vacuum dried at 60°C for 12h to obtain dry bismuth-doped Ag. 2~x Se.

[0040] Embodiment 3

[0041] Lead, Indium doped Ag 2~x Preparation of Se~y mol M (M=In, Pb) based samples, the specific preparation process is as follows:

[0042] Dissolve 4mmol of selenium powder and 6mmol of potassium borohydride in 100mL of deionized water at room temperature and under the protection of 0.01-0.05MPa inert gas, and stir for 5 minutes to obtain a colorless and transparent first solution; at the same time, dissolve 1mol% or 2mol% of lead nitrate or indium nitrate in 10mL of deionized water at a temperature of 20°C and a pressure of 0.01-0.05MPa inert gas protection, then add 7.5-9.0mmol of silver nitrate, stir and dissolve to obtain a clarified second solution; then, quickly pour the cationic solution into the selenium ion solution and quickly move it to a microwave synthesizer, stir at a rate of 1800 rpm, 30°C, and react for 180 minutes. Subsequently, the reaction is completed and the microwave synthesizer is cooled to room temperature, washed and precipitated 3 times with deionized water and ethanol, centrifuged and collected, and the obtained sample is vacuum dried at 60°C for 12h to obtain dry lead, indium-doped Ag 2~x Se.

[0043] Embodiment 4

[0044] Copper-doped Ag 2~x Preparation of Se~y mol M (M=Cu) based samples, the specific preparation process is as follows:

[0045] 4mmol selenium powder and 12mmol potassium borohydride were dissolved in 100mL deionized water at room temperature and 0.01-0.05MPa inert gas protection, and stirred for 5 minutes to obtain a colorless and transparent first solution; at the same time, 100mol% copper nitrate was dissolved in 10mL deionized water at a temperature of 20°C and a pressure of 0.01-0.05MPa inert gas protection, and then 4mmol silver nitrate was added, and a transparent second solution was obtained after stirring and dissolving; then, the cationic solution was quickly poured into the selenium ion solution and quickly moved to a microwave synthesizer, with a stirring rate of 1800 rpm and 30°C, and the reaction was carried out for 180 minutes. Subsequently, the reaction was terminated and the microwave synthesizer was cooled to room temperature, washed and precipitated 3 times with deionized water and ethanol, and centrifuged and collected, and the obtained sample was vacuum dried at 60°C for 12h to obtain dry CuAgSe.

[0046] Embodiment 5

[0047] The Ag2Se-based materials synthesized in Examples 1, 2, 3 and 4 were dispersed in 3 mL of hexane and 3 mL of ethanol, and 0.14 mL of hydrazine hydrate was added, stirred in a glove box for 12 h, then centrifuged and washed twice with ethanol, and dried in vacuo. The obtained sample was then placed in a graphite mold, and hot pressed at 170-180°C and 70-80 MPa for 5 minutes to obtain a high-density Ag2Se-based bulk thermoelectric material.

[0048] The chalcogenide-based thermoelectric materials synthesized in Examples 1, 2, 3 and 4 are black solid powders. The chalcogenide-based thermoelectric materials are phase pure. No second phase impurities are generated after surface treatment in Example 5, and the yield is 80-99%.

[0049] High-temperature tin telluride-based thermoelectric materials

[0050] Embodiment 6

[0051] SnTe thermoelectric material was synthesized by microwave method. The specific preparation process is as follows:

[0052] 2mmol tellurium powder and 6mmol sodium borohydride were dissolved in 10mL deionized water at 20℃ and 50mbar, and a pink transparent solution was obtained after stirring for 120 minutes. Meanwhile, 3mmol stannous chloride and 50mmol sodium hydroxide were dissolved in 100mL deionized water at 100℃ and 0.01MPa inert gas protection to obtain a colorless transparent tin ion solution. Then, the tellurium solution was quickly poured into the tin ion solution and stirred for 30 minutes, and then transferred to a microwave synthesizer and reacted for 50 minutes at 80℃. Subsequently, the reaction was terminated and the microwave synthesizer was cooled to room temperature, washed and precipitated with deionized water and ethanol for several times, collected by centrifugation, and the obtained sample was vacuum dried for 2 hours to obtain SnTe powder.

[0053] Embodiment 7

[0054] Preparation of lead-doped SnTe-based samples. The specific preparation process is as follows:

[0055] 2mmol tellurium powder and 14mmol potassium borohydride were dissolved in 100mL deionized water at 100℃ and 50mbar, and a pink transparent solution was obtained after stirring for 20 minutes. Meanwhile, 3mmol stannous chloride, 0.3mmol lead chloride and 50mmol sodium hydroxide were dissolved in 100mL deionized water at 80℃ and 0.05MPa inert gas protection to obtain a colorless transparent tin ion solution. Then, the tellurium solution was quickly poured into the tin ion solution and stirred for 30 minutes, and then transferred to a microwave synthesizer and reacted at 180℃ for 5 minutes. Subsequently, the reaction was terminated and the microwave synthesizer was cooled to room temperature, washed and precipitated with deionized water and ethanol for several times, and the material was collected by centrifugation. The obtained sample was vacuum dried for 2 hours to obtain Sn. 1-x Pb x Te powder.

[0056] Embodiment 8

[0057] Preparation of Ga-doped SnTe-based samples. The specific preparation process is as follows:

[0058] 2mmol of tellurium powder and 2mmol of lithium borohydride were dissolved in 10mL of deionized water at room temperature and under the protection of an inert gas at a pressure of 0.01MPa, and a pink transparent solution was obtained after stirring for 220 minutes. Meanwhile, 3mmol of stannous chloride, 0.1mmol of gallium chloride and 50mmol of sodium hydroxide were dissolved in 10mL of deionized water at a temperature of 20°C and under the protection of an inert gas at a pressure of 0.05MPa to obtain a colorless transparent tin ion solution. Then, the tellurium solution was quickly poured into the tin ion solution and stirred for 30 minutes, and then transferred to a microwave synthesizer and reacted at a temperature of 80°C for 70 minutes. Subsequently, the reaction was terminated and the microwave synthesizer was cooled to room temperature, washed and precipitated several times with deionized water and ethanol, and the material was collected by centrifugation. The obtained sample was vacuum dried for 2 hours to obtain Sn. 1-x Ga x Te powder.

[0059] Embodiment 9

[0060] The SnTe-based powder materials synthesized in Examples 6, 7, and 8 were dispersed in 1 mL of hexane and 5 mL of methanol, respectively, and 0.14 mL of hydrazine hydrate solution was added, and stirred in an inert atmosphere for 3 hours. The material was centrifugally washed several times with ethanol and deionized water and dried in a vacuum. The dried material was placed in a mold and hot-pressed at 700°C with a pressure of 120 MPa for 30 minutes. In a heater at a temperature of 500°C, the hot-pressed solid was annealed for 6 hours in an inert gas atmosphere to obtain a high-density tin telluride-based bulk thermoelectric material.

[0061] Figure 1 1 is the XRD diagram of the thermoelectric materials prepared by the method of the present invention in Examples 1 and 6. It can be seen from the figure that the structures of the thermoelectric materials prepared by the method of the present invention are respectively orthorhombic silver selenide and cubic tin telluride; further, by comparing the XRD diagrams of the products of Example 6 (SnTe) and Example 9 (anneal) ( Figure 1 (b) to (c)), it can be seen that the preparation method of the present invention can remove the surface oxide by adding a certain amount of hydrazine hydrate.

[0062] Figure 2 It shows that the thermoelectric materials prepared by the present invention all have particle sizes in the nanometer scale.

[0063] Figure 3 The thermoelectric properties of the nanomaterials prepared by the present invention are shown. The thermoelectric materials prepared by the method of the present invention are N-type silver selenide and P-type tin telluride.

[0064] Figure 4 The thermoelectric properties of the products of Example 6 and Example 9 show that the thermoelectric properties of the silver selenide material can be greatly improved by adding a certain amount of hydrazine hydrate.

[0065] In addition, the present invention can also introduce a certain concentration of vacancies into the chalcogenide material. -17 ~10 -19 , and further doped with different elements to reduce the thermal conductivity of the material and increase the Seebeck coefficient of the material, ultimately improving the thermoelectric properties of the material.

[0066] The method of the present invention can prepare pure phase, vacancy-containing and trace metal-doped silver selenide, tin telluride and other thermoelectric materials in one step. At the same time, this method can also be expanded to prepare other chalcogenide compounds.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a chalcogenide-based thermoelectric material, characterized in that: The following steps are involved: (1) preparing a first solution and a second solution, wherein the first solution comprises a chalcogen element or compound and a reducing agent, wherein the concentration of the chalcogen element is 0.01 to 1 mol / L, and the molar ratio of the chalcogen element to the reducing agent is 1:0.5 to 7, and the chalcogen element or compound is at least one of tellurium, tellurium oxide, sodium tellurite, selenium, selenium oxide, sodium selenite, sulfur, sodium sulfide, sodium sulfate, sodium sulfite, and thioacetamide; the second solution comprises a cation source, wherein the concentration of the cation source is 0.01 to 1 mol / L, and the cation source comprises at least one of silver nitrate, a mixture of silver nitrate and bismuth nitrate, a mixture of silver nitrate and lead nitrate, a mixture of silver nitrate and indium nitrate, a mixture of silver nitrate and copper nitrate, a mixture of stannous chloride and sodium hydroxide, a mixture of stannous chloride, sodium hydroxide and lead chloride, and a mixture of stannous chloride, sodium hydroxide and gallium chloride; and the solvent of the first solution and the second solution is deionized water; (2) mixing the first solution and the second solution in a volume ratio of 0.1 to 10:0.1 to 10, placing the mixture in a microwave synthesizer, and reacting the mixture at a temperature of 30 to 300° C. and a stirring rate of 0 to 1800 rpm for 1 to 180 minutes; (3) adding the product obtained in step (2) to a reducing solution for post-treatment for 3-12 hours, and finally washing and centrifuging to finally obtain a sulfide-based thermoelectric material; the solvent of the reducing solution is a mixture of a non-polar solvent and a polar organic solvent in a volume ratio of 0.1-10:0.1-10; the solute is at least one of sodium borohydride, potassium borohydride, hydrazine hydrate, and lithium borohydride; the mass ratio of the solute to the two solvents is 0.001-0.5:1-5:1-5.

2. The method according to claim 1, characterized in that In the mixture of silver nitrate and bismuth nitrate, the mixture of silver nitrate and lead nitrate, and the mixture of silver nitrate and indium nitrate, the molar ratio of silver nitrate to bismuth nitrate, lead nitrate, indium nitrate or copper nitrate is 1:0.001-0.

05.

3. The method according to claim 1, characterized in that In the mixture of stannous chloride and sodium hydroxide, the mixture of stannous chloride, sodium hydroxide and lead chloride, and the mixture of stannous chloride, sodium hydroxide and gallium chloride, the molar ratio of stannous chloride to sodium hydroxide is 1:2-30.

4. The method according to claim 1, characterized in that: It also includes hot pressing and sintering steps: The obtained sulfide compound-based thermoelectric material is placed in a fixed shape mold, and a pressure of 10 to 220 MPa is applied at a temperature of 100 to 1000° C. for 0.1 to 60 minutes; then, the material is thermally stabilized at a temperature of 50 to 800° C. in an inert gas atmosphere for 0.1 to 12 hours, and the molded sulfide compound-based thermoelectric material is obtained by demolding.

5. The method according to claim 1, characterized in that The first solution is prepared by the following method: adding a sulfide element or compound to deionized water at 20-100° C. and a pressure of 50 mbar or under an inert gas protection pressure of 0.01-0.05 MPa until dissolved to obtain a first solution; The second solution is prepared by the following method: Under the conditions of 20-100° C. and 50 mbar pressure or under the protection of an inert gas with a pressure of 0.01-0.05 MPa, a cation source is added to deionized water until it is dissolved to obtain a second solution.

6. The method according to claim 1, characterized in that The reducing agent is at least one of sodium borohydride, potassium borohydride, hydrazine hydrate and lithium borohydride.

7. The method according to claim 1, characterized in that The chalcogenide-based thermoelectric material is a black solid powder, is phase-pure, has no second-phase impurities after surface treatment, and has a yield of 80-99%.

8. A chalcogenide-based thermoelectric material prepared according to the method according to any one of claims 1 to 7, characterized in that: The chalcogenide-based thermoelectric material is an N-type / P-type thermoelectric material, and no P-to-N-type transition occurs before the phase change process.

Citation Information

Patent Citations

  • Preparation method of silver-based chalcogenide Ag2X thermoelectric material

    CN111252802A